Physical function of the upper limb after breast cancer surgery. Results from the SOUND (Sentinel node vs. Observation after axillary Ultra-souND) trial. Issue 5 (May 2016) - Gentilini, O.; Botteri, E.; Dadda, P.; Sangalli, C.; Boccardo, C.; Peradze, N.; Ghisini, R.; Galimberti, V.; Veronesi, P.; Luini, A.; Cassano, E.; Viale, G.; et al.
Abstract: Background: The SOUND (Sentinel node vs. Observation after axillary Ultra-souND) trial is an ongoing prospective randomized study comparing sentinel node biopsy vs. no axillary surgical staging in patients with small breast cancer and negative pre-operative ultra-sound of the axilla. Patients and methods: The first 180 recruited patients were administered the Quick DASH (Disability Arm and Shoulder) questionnaire at different time points (before surgery, 1 week, 6 months and 1 year after surgery) to evaluate the physical function of the ipsilateral upper limb, The Quick DASH score ranges from 0 (no disability) to 100 (complete disability). Results: 176 patients were available for analysis (94 in SNB arm and 82 in observation arm). The two groups were comparable with respect to age, tumor characteristics and treatments. Pre-surgery score values were 3.0% and 2.7% in the SNB arm and observation arm, respectively (P = 0.730). One week after surgery, the score increased to 24.0% in the SNB arm and 10.6% in the observation arm (P < 0.001). After 6 and 12 months, the score decreased in both arms to values similar to baseline values. The overall trend in time of the score was significantly different between the two arms (P < 0.001), even after the exclusion of five patients who received AD in the SNB arm (P < 0.001). Conclusions: Patients who underwent SNB had a significantly higher rate of disability in the early post-operative period compared to patients who did not. The avoidance of SNB might translate into a considerable reduction of physical and emotional distress.